Contribution of paranasal sinus, chest, and abdomen/pelvis computed tomography in patients with febrile neutropenia - Charles Tran; Éric de Kerviler; Anne Bergeron; Emmanuel Raffoux; Aliénor Xhaard; Cédric de Bazelaire; Constance de Margerie-Mellon (PLoS ONE, 2025)
Objective Febrile neutropenia (FN) is a serious clinical event, associated with significant morbidity and mortality. Imaging has a central role in the identification of the fever cause. The study objectives were to assess abnormalities of potential infectious origin on paranasal sinus, chest and abdomen/pelvis CT scans performed during an episode of FN, in patients with or without specific clinical signs, and to evaluate their impact on the frequency of changes in treatment. Materials and methods This retrospective study included 306 patients with FN from a single academic center between October 2018 and December 2019. Clinical and biological data, final clinical diagnosis for the FN episode, and change in treatment following CT scans were collected from medical records. CT images were reviewed for positive findings in each anatomical region. Results Overall, 188 patients (61.4%) had at least one positive CT finding on paranasal sinus, chest and/or abdomen/pelvis regions, and 153 patients (50.0%) received a final clinical diagnosis of infection, based on microbiological and/or radiological findings. There were more chest and abdomen/pelvis CT positive findings in patients with specific clinical signs than in patients without (65.7% vs. 25.8%, and 59.0% vs. 22.7% respectively, p <0.001), with a higher frequency of therapeutic modifications in positive CTs. There were significantly more paranasal sinus CT abnormalities in symptomatic patients (33.3% vs. 8.5%, p = 0.03), but without any impact on treatment. Conclusion These results support recommendations to perform systematic chest CT in patients with FN and may encourage the widespread use of abdomen/pelvis CT in this indication, even without symptoms. However, the actual impact of their use on the prognosis of the patients remains to be evaluated.